CARACTERIZAÇÃO METROLÓGICA DE UM MEDIDOR VOLUMÉTRICO PARA PEQUENAS TAXAS DE FLUXO DE GÁS UTILIZANDO O MÉTODO DE DIFERENÇA DE PRESSÃO - Abreu, Pedro Augusto Lopes (2011)
A system for measuring low rates of gas flow has great importance for some industrial and especially for scientific applications where usually high accuracy and low uncertainty are required. This type of measurement systems have undergone a great development in recent years primarily due to the concern with the release of gases in natural processes occurring in the environment, such as anaerobic biodegradation process which releases methane and the use in the production of biogas. In this work, the development of low-volume gas flow rate measurement system using the method of pressure difference in a container of known volume is presented. A microcontroller is used to control two valves located one gas inlet and the other at the gas outlet of the container. Appropriate analysis of uncertainty propagation is carried out, and components suitable are selected for the development of the meter in order to perform the measurement with low uncertainty. Simulations and experimental tests are presented for validating the proposed system.